Assessment the risk of destruction the cultural layers on the territory of medieval Pechersk Monastery related to landslide genesis - Tustanovska, Liubov; Nesterovskyi, Viktor; Taranenko, Sergiy; Cherevko, Iryna; Makhota, Olena (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
In 2016, a modern Archaeological map of the territory of the Kyiv Pechersk Lavra National Preserve (NR KPL) was developed, serving as a foundation for conducting research aimed at the preservation of the diverse cultural layers of this unique complex, spanning the period from the 11th to the 19th centuries. The Preserve is situated on the distinctive Pechersk Hill whose formation is influenced by dynamic natural and man-made factors that adversely affect the feature’s environment. Since the terrain acts as an indicator of the complex interaction of these processes, its detailed analysis provides an effective means for investigating the slope’s evolution. The objective of this study is to construct digital models of the paleorelief integrated with the existing Archaeological Map of the NR KPL, and to establish a database for risk assessment within the excavation zones. A structural and morphometric analysis served as the principal methodological tool. Among the numerous results obtained, the most informative were the quantitative and qualitative characteristics of the residual relief (forecast) maps, and the differential maps between the summit and base surfaces (dynamic maps). These outputs enabled the reconstruction of the detailed evolution of the slopes, the identification of areas of active erosion, and the assessment of the potential risk zones at the archaeological and architectural sites, notably the Dormition Cathedral (K-80), the Church of the Saviour at Berestove (K-84), the Church of the Nativity of the Virgin Mary (K-59), and other features.